Carica Papaya Leaf Extracts to Accelerate Platelet Count in Dengue Fever - Koirala, Manisa (Journal of Nursing Education of Nepal, 2023)
Dengue is the most extensively emerging mosquito-borne viral disease, caused by an arbovirus through the bite of an infected Aedesaegypti mosquito found in tropical and sub-tropical regions around the world. Expansion of its endemics in more than 100 countries towards new territories in the hilly regions even in Nepal is a serious concern. The symptoms include mild to severe form characterized by high fever, rash, severe headache, severe joint & muscular pain, nausea, vomiting, and eye pain. It is usually a self-limited illness, and no specific antibiotic or antiviral treatment seems indicated only require to provide supportive care. The Carica Papaya Leaf Extracts (CPLE) has proposed to have beneficial in improving platelet counts and minimize symptoms as evidence by several studies.
Keywords: Carica Papaya; Dengue; Mosquito borne; Viral disease